Perception of barriers in setting up student spin-offs - Abdul Rahman, Zahari; Noor Azlinna, Azizan (American Scientific Publishers, 2018)
University spin-off has captured the attention of policymakers, educators and researchers in the last few decades due to its contribution to economic growth, innovation, development and employment generation in many countries worldwide. This study intent to investigate the perception of barriers in setting up student spin-offs (a type of university spin-off) through extensive literature reviews. Previous studies had mentioned greater contributions of student spin-offs as compared to other type of university spin-off called academic spin-offs and led this study to be conducted. A systematic literature review is conducted with several scientific articles and reports have been examined. The results indicate that there are seven main sets of barriers encountered by university students to set up spin-offs. Among the barriers are: Barrier 1 (lack of capital or financial); Barrier 2 (risk or fear of failure); Barrier 3 (lack of skills and supports) Barrier 4 (lack of education or knowledge); Barrier 5 (tax law or legal and lack of self-efficacy or social supports); Barrier 6 (lack of networking, culture, and operating risks); Barrier 7 (regional barriers- level of competitions, political or economic climate, lack of role models, crimes or corruptions level, and poor institutions). Moreover, this study also has outlined some possible solutions to reduce the perception of barriers to form student spin-offs. This study will serve as a base for future studies and will have valuable implications for policymakers and universities.